187: EFFECT OF PERI-OPERATIVE CHEMOTHERAPY REGIMEN ON SURVIVAL IN THE TREATMENT OF LOCALLY ADVANCED GASTRO-OESOPHAGEAL ADENOCARCINOMA—FLOT VS 'MAGIC'. (23rd April 2022) - Moore, J; Kumar, S; Patel, P; Santaollala, A; Kapiris, M; Van Hemelrijk, M; Maisey, N; Lagergren, J; Gossage, J; Kelly, M; Baker, C; Allum, W; et al.
Abstract: Background and aim: Peri-operative chemotherapy has been shown to improve survival in patients with locally advanced oesophago-gastric adenocarcinoma. Two commonly used regimens are epirubicin, cisplatin plus capecitabine or fluorouracil (MAGIC) and fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT). The primary aim of this study was to evaluate the effect of chemotherapy regimen (FLOT vs MAGIC) on survival. We also aimed to assess pathological response, surgical complications, chemotherapy associated adverse events and chemotherapy completion rates. Methods: Cohort study including 946 patients treated with peri-operative FLOT or MAGIC chemotherapy who underwent oesophagectomy or gastrectomy for oesophageal or gastric adenocarcinoma between 2002–2021 at St Thomas' Hospital, London, UK or The Royal Marsden Hospital, London, UK. Survival analysis was performed using Kaplan–Meier and Cox regression. Results: Patients treated with MAGIC had worse overall and disease-free survival compared with FLOT on multivariable analysis (overall survival HR 1.353 95% CI 1.039–1.763, disease-free survival HR 1.335 95% CI 1.025–1.739). Stratified analysis by tumour location revealed similar results for both oesophageal and gastric tumours. Patients treated with FLOT were more likely to have a favourable pathological response (Mandard 1–2) (11.1% MAGIC vs 21.8% FLOT, P < 0.001). Patients treated with FLOT were less likely to have a positive resection margin (19.1% FLOT vs 32.2% MAGIC, P < 0.001). Surgical complications, chemotherapy associated adverse events and chemotherapy completion rates were comparable between groups. Conclusion: Patients with oesophageal and gastric adenocarcinoma treated with peri-operative FLOT had improved survival compared with those treated with peri-operative MAGIC. Surgical complications, chemotherapy associated adverse events and chemotherapy completion rates were comparable between groups. Table: https://secure.sem-2000.it/semUpload/OLC/file/9203828791100911681076702/94509_Table.jpg .